EFEK MODERASI KESADARAN WAJIB PAJAK DALAM HUBUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK DAN KEPATUHAN MEMBAYAR PAJAK - muhamad safiq (Accounthink, 2020)
The purpose of this study is to examine the role of taxpayer awareness of the factors that affect taxpayer compliance for micro, small and medium enterprises (MSMEs). The research sample was taken from the taxpayers of UMKM actors who were in the Bekasi - West Java area. This study used 120 respondents (samples), which were taken by purposive sampling method. Furthermore, researchers used a structural equation model analysis tool with the WrapPLS 5.0 system to test the hypothesis. The results showed that the understanding of taxpayers on PP No. 46/2013 and tax sanctions partially affected taxpayer compliance. Meanwhile, the taxation system and the quality of tax authorities have no effect on taxpayer compliance in paying taxes. The next result shows that taxpayer awareness does not moderate the relationship between taxpayer understanding of PP 46 of 2013 and taxpayer compliance. However, taxpayer awareness is able to influence (moderate) the relationship between the tax system, service quality and tax sanctions on taxpayer compliance. These results indicate that in general taxpayer awareness is able to play a role in increasing taxpayer compliance.